2003
DOI: 10.1021/la026989f
|View full text |Cite
|
Sign up to set email alerts
|

Long Chain n-Alkanes at SiO2/Air Interfaces:  Molecular Ordering, Annealing, and Surface Freezing of Triacontane in the Case of Excess and Submonolayer Coverage

Abstract: We present a comprehensive study on the interfacial molecular ordering of an n-alkane, triacontane, at the SiO2/air interface, for submonolayer and excess coverage. The molecular ordering was studied by X-ray diffraction and reflectivity at temperatures from far below bulk melting to above the surface freezing temperature. It is found that the phase behavior of bulk and that of interfacial triacontane are quite different. From the literature it is known that bulk triacontane has three solid phases: one crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 51 publications
5
30
0
Order By: Relevance
“…These changes indicate a transition in the film from the orthorhombic structure described above to a phase characterized by a higher symmetry (probably a hexagonal structure) and much a shorter coherence length than in the lowtemperature C phase. Following previous suggestions of a rotator phase for interfacial alkane molecules of intermediate length [9,10], we interpret the changes in the X-ray scans in the range 56-58…”
Section: -P2mentioning
confidence: 71%
“…These changes indicate a transition in the film from the orthorhombic structure described above to a phase characterized by a higher symmetry (probably a hexagonal structure) and much a shorter coherence length than in the lowtemperature C phase. Following previous suggestions of a rotator phase for interfacial alkane molecules of intermediate length [9,10], we interpret the changes in the X-ray scans in the range 56-58…”
Section: -P2mentioning
confidence: 71%
“…12 On top of this bilayer, molecules with their long axis perpendicular to the surface coexist with monoclinic and orthorhombic bulk particles. 13,14 The mesa-shaped orthorhombic particles are surrounded by an area depleted of perpendicular layers. 4,15 Moreover, Bai et al 4 have recently shown that thin films of intermediate-length alkanes do not completely wet SiO 2 surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Schollmeyer et al 13 conducted a comprehensive study of triacontane ͑n-C 30 H 62 or C30͒ films grown by spin coating on solid substrates. From their x-ray diffraction measurements, they found that some of their thin films had a different number of solid phases than the bulk material and suggested that these additional phases were stabilized by interfacial interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Riegler and co-workers [5][6][7][8] have proposed that a similar surface freezing effect can occur with intermediate-length alkane molecules if air is replaced by a solid substrate ͑SiO 2 ͒. In their model of a thick alkane film, a crystalline monolayer of perpendicularly oriented alkane molecules adsorbs immediately adjacent to the SiO 2 surface.…”
Section: Introductionmentioning
confidence: 99%